Pengaruh E-Commerce, Inovasi Dan Sosial Media Terhadap Pendapatan UMKM (Studi Kasus Pada Toko Pakaian di Kecamatan Sako Palembang) - Resti Marsela; Lili Syafitri; Andini Utari Putri (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
Income is the income earned or received by a person or household from a business or job. Financial behavior is influenced by various factors, including e-commerce, innovation and social media. This research aims to examine the influence of commerce, innovation and social media on MSME income at clothing stores in Sako District. This research is a quantitative descriptive type with primary data sources originating from distributing questionnaires. The population in this research is MSMEs in clothing stores in Sako sub-district, Palembang. The number of samples in this research was 97 MSME units using the Slovin formula. The sampling technique uses a non-probability method with purposive sampling technique. The analysis technique in this research uses multiple linear regression, coefficient of determination, t test and F test. The results of this research show that e-commerce (X1) has a positive and significant effect on MSME income (Y). Innovation (X2) has a positive and significant effect on MSME income (Y). Social Media (X3) has a positive and significant effect on MSME income (Y). E-Commerce, innovation and social media simultaneously have a positive and significant effect on MSME income.